Biflavonoid Profiling of Juniperus Species: The Influence of Plant Part and Growing Location - Barbara Medvedec; Iva Jurčević Šangut; Armin Macanović; Erna Karalija; Dunja Šamec (Applied Sciences, 2025)
Biflavonoids are an important group of flavonoids found in Juniperus species, yet their distribution and accumulation patterns remain insufficiently explored. In this study, we applied a method for the simultaneous quantification of seven biflavonoids to analyze different plant parts of J. communis, J. communis subsp. nana, and J. oxycedrus. In order to determinate the influence of growing location, we also analyzed J. communis samples collected from different locations. Four biflavonoids—cupressuflavone, amentoflavone, bilobetin, and hinokiflavone—were detected. In both analyzed J. communis varieties, amentoflavone was the predominant biflavonoid in cones and needles, while in J. oxycedrus, cupressuflavone was the most abundant in cones, with amentoflavone dominating in needles. Overall, biflavonoid content was significantly higher in needles than in cones, with total biflavonoid levels in needles exceeding 5 mg/g dw, highlighting the tissue-specific nature of biflavonoid biosynthesis within Juniperus species. Additionally, our results suggest that in J. communis, biflavonoid accumulation is significantly influenced by growing location.